THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE HEALTH OFFICE OF SERANG DISTRICT - Fahri Rokhman; Eloh Bahiroh; Vera Maria (Bajang Institute, 2022)
This study aims to determine the effect of transformational leadership style, motivation and work discipline on the performance of Serang district health office employees. The type of research used is quantitative with a descriptive approach, the population in this study is the office of the health office totaling 105 people. The sample of this study amounted to 52 respondents. The research instrument trials were carried out at the Serang Health Office office staff, with random sampling, and in measuring the questionnaire using a measurement scale of 1-10, the data analysis methods used were data quality tests, outer model tests and inner models with the help of SmartPLS version 3.0 software. . 1. The results showed that the transformational leadership style had a positive and insignificant effect on employee performance. This is evidenced by the original sample value of 0.027. From the results of data processing, the t-statistic value is smaller than the t-table value (0.309 > 1.96) with a p-value of 0.758, then the first hypothesis is rejected. The results showed that work motivation had a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.457. From the results of data processing, the t-statistic value is greater than the t-table value (4.834 > 1.96) with a p-value of 0.000, then the second hypothesis is accepted. The results showed that work discipline had a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.476. From the results of data processing, the t-statistic value is greater than the t-table value (4.338> 1.96) with a p-value of 0.000, then the third hypothesis is accepted.